Factors Affecting Investment Decisions by Muslim Investors in the Indonesia Islamic Capital Market: An Application of Theory of Planned Behavior - Wuladari MA, Ratu Ayu Sri Wulandari; Sani, Irma Harisha; Pramuka, Bambang Agus (Faculty of Economics and Business, Jenderal Soedirman University, 2023)
The Islamic capital market is a capital market whose entire mechanism of activity has been adapted to Sharia principles. Indonesia, as a country with a majority Muslim population, the Islamic capital market should have great potential to develop. However, the number of investors in the Sharia capital market is still low. This study examines the effect of financial literacy, subjective norms and technological advances on investment decisions using the Theory Of Planned Behavior (TPB). The study was conducted on 150 Sharia stock investors who are members of the